Annotated checklist of the Blennidus subgenus Agraphoderus species from Peru with description of B. bombonensis n. sp. and synonymic notes (Coleoptera: Carabidae: Pterostichinae) - Allegro, Gianni; Giachino, Pier Mauro (Zootaxa, 2015)
Forty species belonging to the subgenus Agraphoderus of Blennidus have been recorded so far from Peru. An annotated checklist is provided with information about their type locality, distribution and habitat. The nomenclature of each species is also provided, together with some notes on their systematic status. Blennidus bombonensis n. sp. from Cerro de Pasco is described; Blennidus pseudangularis nomen novum for Ogmopleura angularis Straneo, 1993 (nec Straneo, 1985) is proposed and the following synonymies are stated: Blennidus pseudangularis Allegro & Giachino, nomen novum = Blennidus rectangulus (Straneo, 1993) syn. nov.; Ogmopleura minor Straneo, 1993 = Blennidus rectangulus (Straneo, 1993) syn. nov. Type specimens of most species are illustrated, as well as male genitalia. Finally, a revised key to all the Agraphoderus species from Peru is provided.